THE ROLE OF ARTIFICIAL INTELLIGENCE IN BUSINESS PROCESS OPTIMISATION IN ECONOMY 5.0 - Loso Judijanto; Ahmad Rizani (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
In the era of Economy 5.0, artificial intelligence (AI) plays a critical role in business process optimisation aimed at improving operational efficiency, analytical data utilisation, and competitive advantage. AI enables automation of routine tasks, reduces operational costs, and improves productivity by minimising human errors. In addition, AI strengthens a company's analytical capabilities through predictive data analysis, which helps in smarter decision-making and responsiveness to market dynamics. Overall, the adoption and investment in AI technology is an important strategic step for companies to face the challenges and opportunities of the Economy 5.0 era, as well as to improve customer service and adaptability to market changes.